Work history and diagnosed hypertension among older adults in Ghana: evidence from WHO SAGE Wave2 - Otieku, Evans; Patche, Cecilie Blenstrup; Katibeh, Marzieh; Awalime, Dziedzom; Mohammed Gyasi, Razak (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction There is limited knowledge in the context of Africa on how work history associates with hypertension at old age. Therefore, this paper analyses such an association using Ghana as a case study. Methods Data from the World Health Organisation Study on Global AGEing and Adult Health Wave 2 was used to explore the relationship between work history and diagnosed hypertension at old age. In the Wave2 study, a multistage cluster sampling was used to select participants at the household level across rural/urban areas in all administrative regions. A multifactor logit regression analysis was performed. The paper also estimated diagnosed hypertension prevalence across subgroups. Results The mean age of the total of 3564 participants examined was 64 years (SD = ±10years). The overall prevalence of hypertension was 10.3% [95% CI = 9.4–11.1]. The highest predicted rate was 41.1% [95% CI=38.0 – 49.2] among those who stopped working before the statutory retirement age 60 years, whereas it was only 4% [95% CI = 3.7 – 5.2] for those who retired from active work at age 60 years. Those who retired at age <60years recorded the highest risk of hypertension diagnosis [OR = 14.1; 95% CI=10.5-19.5]. There was also a significant association between diagnosed hypertension and a history of working <5 days per week [OR=1.6; 95% CI=1.1-2.3]. It emerged that those with a history of informal sector employment were at significant risk of hypertension at old age, if they worked <5days per week [OR=1.5; 95% CI=1.0-2.3]. Conclusions Overall, retirement age emerged as a significant risk factor for diagnosed hypertension at old age, followed by a history of less than five working days per week.